Characterization of thermal and acoustic insulation of chicken feather reinforced composites. (2017) - Bessa, João; Souza, Jefferson; Lopes, J.B.; Sampaio, José; Mota, Calos; Cunha, Fernando; Fangueiro, Raúl
Abstract: This work evaluates the application potential of chicken feather fibres in the reinforcement of polymeric materials, particularly thermosetting ones as epoxy resins. Due to the morphology of this type of protein fibres, which is characterized by being hollow, its study and application has particular interest as components being able to contribute for the thermal insulation, once air is well known as a bad heat conductor. Composite materials were produced using compression moulding process, and subsequently thermal and acoustic insulation tests were performed to evaluate the influence of chicken feather fibres as potential reinforcements for thermal and acoustic insulation composites applications. The experimental results show that the chicken feather fibres present high potential to be applied as reinforcement in composite materials. It was verified that the thermal resistance of composite materials is favourably dependent on the chicken feather fibres mass fraction, being registered a value of 0.175 m 2 K W -1 when an 80:20 ratio (chicken feather fibre and epoxy resin, respectively) was used. Moreover, comparing with coir fibres reinforcing polypropylene, it was verified a better performance, once this composite material just revealed a thermal resistance around 0.114 m 2 K W -1 .